Coupling Topological Insulator SnSb2Te4 Nanodots with Highly Doped Graphene for High‐Rate Energy Storage. Issue 2 (28th November 2019) - Wu, Zhibin; Liang, Gemeng; Pang, Wei Kong; Zhou, Tengfei; Cheng, Zhenxiang; Zhang, Wenchao; Liu, Ye; Johannessen, Bernt; Guo, Zaiping
Abstract: Topological insulators have spurred worldwide interest, but their advantageous properties have scarcely been explored in terms of electrochemical energy storage, and their high‐rate capability and long‐term cycling stability still remain a significant challenge to harvest. p‐Type topological insulator SnSb2 Te4 nanodots anchoring on few‐layered graphene (SnSb2 Te4 /G) are synthesized as a stable anode for high‐rate lithium‐ion batteries and potassium‐ion batteries through a ball‐milling method. These SnSb2 Te4 /G composite electrodes show ultralong cycle lifespan (478 mAh g −1 at 1 A g −1 after 1000 cycles) and excellent rate capability (remaining 373 mAh g −1 even at 10 A g −1 ) in Li‐ion storage owing to the rapid ion transport accelerated by the PN heterojunction, virtual electron highways provided by the conductive topological surface state, and extraordinary pseudocapacitive contribution, whose excellent phase reversibility is confirmed by synchrotron in situ X‐ray powder diffraction. Surprisingly, durable lifespan even at practical levels of mass loading (>10 mg cm −2 ) for Li‐ion storage and excellent K‐ion storage performance are also observed. This work provides new insights for designing high‐rate electrode materials by boosting conductive topological surfaces, atomic doping, and the interface interaction. Abstract : Topological insulator SnSb2 Te4 nanodots coupled with few‐layered graphene show excellent rate capability and durable cycling performance for pseudocapacitive Li‐ion and K‐ion storage. They achieve this through boosting the conductive topological surfaces, atomic doping, and interface interaction, benefitting from the rapid ion transport accelerated by the PN heterojunction, virtual electron highways provided by the conductive topological surface state, and extraordinary pseudocapacitive contribution.